Culturally safe mental healthcare - McGough, Shirley (2016)
Cultural safety holds a great opportunity in transforming culturally appropriate healthcare for Aboriginal Australians (Taylor and Guerin, 2010). However the experiences of non- Aboriginal health professionals in providing culturally safe mental healthcare is not well documented. Therefore it is critical that culturally safe care in this setting is explored.